A Mimetic Assay of Neutrophil Extracellular Trap Degradation Using YOYO-1-Stained DNA-Histone Surface Webs - Katherine H. Nguyen; Midori L. Wasielewski; Srilakshmi Yalavarthi; Xianggui Qu; Jason S. Knight; Shuichi Takayama (Cells)
Neutrophil extracellular traps (NETs) are not only promising biomarkers of disease, but also potential therapeutic targets. Overproduction or the improper clearance of NETs has been linked to disease severity. In vitro NET degradation assays can reveal mechanisms and degradation efficiency differences in diseased serum samples. There is a need for more convenient assays to increase the speed of NET degradation studies. This paper describes a simplified, lower variability mimetic assay with DNA–histone structures, referred to as surface webs, that performs functionally similarly to traditional NET degradation assays with increased scalability, ease of use, shorter preparation time, and lowered costs. The surface webs are created and dehydrated in a 96-well microplate that is shelf-stable, transportable, and viable for 30 days of storage at room temperature. The surface webs, compared to NETs, have similar shapes and distribution but lower intraplate variability while degrading with healthy serum and DNase I within the same timeframe. The assay can identify patient serum with reduced degradation capabilities. This assay opens new opportunities for NET-targeted drug discovery and studies on the role of NETs as modulators of disease.